2018
DOI: 10.5312/wjo.v9.i9.130
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of palmar subcutaneous tissue vascularization in patients with Dupuytren’s contracture

Abstract: AIMTo investigate the structural and functional characteristics of palmar hypodermal tissue vascularization in Dupuytren’s contracture patients of different age groups.METHODSEighty-seven Dupuytren’s contracture patients underwent partial fasciectomy. Twenty-two of them were less than 55 years old (Y-group, n = 22); the others were 55 and older (O-group, n = 65). In surgically excised representative tissue samples, a histomorphometric analysis of the perforating arteries of the palmar aponeurosis and stereolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The number of macrophages in the disease tissue is correlated with the presence of myofibroblasts [83], which are indicative of active disease. As with other fibrotic conditions, the growths show increased vascularization [57]. The pro-survival, pro-proliferative signaling of IL-6 and its downstream effector cytokines likely contribute to the microenvironment conducive to angiogenesis.…”
Section: Dupuytren's Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…The number of macrophages in the disease tissue is correlated with the presence of myofibroblasts [83], which are indicative of active disease. As with other fibrotic conditions, the growths show increased vascularization [57]. The pro-survival, pro-proliferative signaling of IL-6 and its downstream effector cytokines likely contribute to the microenvironment conducive to angiogenesis.…”
Section: Dupuytren's Diseasementioning
confidence: 96%
“…Vascularization is an important component of wound healing, and impaired vascularization delays wound closure [55]. However, the dysregulation of vascularization, potentially through the expression VEGF, may be a component of fibrotic disease pathogenesis, as many fibrotic diseases, much like proliferative neoplasms, feature increased vascularization [56,57].…”
Section: Proliferationmentioning
confidence: 99%
“…No studies relating to vascularization in pathological longitudinal and vertical septa have been published in the literature. Shchudlo and coauthors (2018) investigated the structural and functional characteristics of palmar hypodermal tissue vascularization in Dupuytren's diseased patients of different age groups, demonstrating that the younger group exhibited more severe constrictive remodelling of the palmar fascia in perforating the arteries supplying the hypodermis compared with the older patients, with more compensatory changes of its capillarization [16]. Holzer and coauthors (2013) demonstrated a higher expression of HIF-1α (hypoxia-inducible factor alfa) and VEGFR2 (vascular endothelial growth factor receptor 2), statistically significant compared to the controls, in the Dupuytren's diseased tissue of palmar aponeurosis: the subsequent hypoxic conditions and angiogenesis are fundamental stimulators of fibrosis, indicating their participation in the myofibroblast-rich nodules as active disease processes [17].…”
Section: Discussionmentioning
confidence: 99%
“…The disease mostly affects men > 40 years of age. 4,5 Heavy alcohol consumption, smoking, and exposure to manual work showed a positive dose-response relationship with the prevalence of DD. 5,6 The pathogenesis involves abnormal myofibroblastic growth in the fasciae of the hand.…”
mentioning
confidence: 98%